Immunosuppressive Tumor Microenvironment Status and Histological Grading of Endometrial Carcinoma - Antomarchi, Julie (Cancer Microenviron, 2019)
The recent successes of new cancer immunotherapy approaches have led to investigate their relevance in the context of the Endometrial Carcinoma (EC). These therapies, that take the tumor-induced immunosuppressive microenvironment into account, target the tumor immune escape, in particular the inhibitory receptors involved in the regulation of the effector T cells’ activity (immune checkpoints). The aim of this study was to identify, in ECs, differences in intergrades immune status that could contribute to the differences in tumor aggressiveness, and could also be used as theranostic tools. The immune status of tumors was assessed by quantitative real-time PCR. We analyzed the expression of specific genes associated to specific leukocytes subpopulations and the expression of reporting genes associated with the tumor escape/resistance. This study highlights significant differences in the EC intergrades immune status especially the tumor-infiltrating cell types and their activation status as well as in the molecular factors produced by the environment. The immune microenvironment of grade 1 ECs hints at a robust tumoricidal milieu while that of higher grades is more evocative of a tolerogenic milieu. This genes-based immunological monitoring of tumors that easily highlights significant intergrade differences relating to the density, composition and functional state of the leukocyte infiltrate, could give solid arguments for choosing the best therapeutic options, especially those targeting immune checkpoints. Moreover it could enable an easy adaptation of individual treatment approaches for each patient. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12307-019-00225-1) contains supplementary material, which is available to authorized users.